Orientasi Kewirausahaan, Penciptaan Nilai Melalui Daya Saing Dalam Meningkatkan Kinerja BUMDes Di Kabupaten Kuningan - Suhardi, Dadang; Gunawan, Wely Hadi; Watulandi, Micki (Valid: Jurnal Ilmiah, 2025)
This study aims to analyze the effect of entrepreneurial orientation and value creation on the performance of village-owned enterprises (BUMDes), with competitiveness as a mediating variable. The research adopts a quantitative approach with descriptive and explanatory design. Data were collected through questionnaires and in-depth interviews and analyzed using Structural Equation Modeling (SEM) with AMOS software. The study population consists of 361 BUMDes in Kuningan Regency, with 100 respondents selected using purposive sampling techniques. The findings indicate that entrepreneurial orientation and value creation significantly influence competitiveness, which positively impacts BUMDes performance. However, the direct effect of entrepreneurial orientation on BUMDes performance is insignificant. These results highlight the importance of synergy between entrepreneurship, value creation, and competitiveness in BUMDes development. The study provides strategic recommendations to enhance BUMDes performance through training, technology-based innovation, and collaboration with various stakeholders